2007
DOI: 10.1310/hct0801-19
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of a Novel Short-Cycle Antiretroviral Treatment Interruption Strategy: 48-Week Results of the Five-Days-On, Two-Days-Off (FOTO) Study

Abstract: If validated, the FOTO treatment strategy with efavirenz-based regimens could avoid the viremia witnessed in longer cycle structured treatment interruptions yet still ameliorate a number of problems associated with the current paradigm of daily ART for HIV infection, including the high cost of therapy and the pill fatigue that, in many patients, leads to erratic adherence and ultimately treatment failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 10 publications
7
42
0
Order By: Relevance
“…On study days 10 to 13, darunavir and ritonavir plasma concentrations were assessed predose and at 1, 2, 3, 4,6,8,10,12,16,20,24,30,36,48,60, and 72 h postdose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On study days 10 to 13, darunavir and ritonavir plasma concentrations were assessed predose and at 1, 2, 3, 4,6,8,10,12,16,20,24,30,36,48,60, and 72 h postdose.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study found that doses might be missed in the case of regimens containing long-half-life drugs, such as the nonnucleoside reverse transcriptase inhibitor (NNRTI) efavirenz (8). However, the strategy appeared much riskier for patients on protease inhibitors like lopinavir-ritonavir or saquinavirritonavir that achieved subtherapeutic drug concentrations at the end of the second day off therapy, suggesting that despite the presence of the ritonavir boosting effect, lopinavir and saquinavir plasma concentrations declined rapidly (7).…”
mentioning
confidence: 99%
“…Of those on a nonboosted regimen, one was on nonboosted atazanavir while two were on ritonavir and seven were on nelfinavir. The following NRTIs were used: zidovudine (13), lamivudine (16), tenofovir (9), stavudine (7), didanosine (8), and emtricitabine (4). There was one subject also on T-20.…”
Section: Regimens and Resistance Genotypingmentioning
confidence: 99%
“…15 Cohen and colleagues studied a strategy of five days on-two days off (FOTO) strategy with overall good viral control in 89.6% of subjects with 100% virologic control in subjects on an efavirenz-based HAART regimen. 16 As adolescents and young adults face a lifetime of HAART once meeting guidelines, a short-cycle management approach is particularly appealing in this population to limit ART exposure as well as potentially impact on long-term adherence. The Adolescent Trials Network 015 study was a proof of concept study of a 4-day on=3-day off short-cycle therapy in adolescents and young adults, on a protease inhibitor-based HAART regimen, who demonstrated good viral control for at least 6 months and CD4 þ T cells above 350 cells=mm 3 at study entry.…”
Section: Introductionmentioning
confidence: 99%
“…Our study of short, intermittent antiviral treatment cycles of 4 days per week [1 step down from the previously administered 5 day per week regimen (29)] struck a bonanza: 94 patients took intermittent therapy for 157 cumulated years, i.e., 87 treatment weeks per patient, 63 patients having passed 2.5 intermittent treatment years. It should be noted that despite archived, resistant viruses from past failures in 25 patients or the administration of half of the daily recommended dose of a drug base in 11 patients, there was not 1 viral escape over 8164 weeks.…”
Section: Iccarre 4 Day Per Week Treatment: Not a Single Hiv Escapementioning
confidence: 99%